Concepts and forms of special knowledge implemented during the investigation of criminal offenses related to raiding - Chalyi, Bohdan (Archives of Criminology and Forensic Sciences, 2025)
Relevance of the problem of countering raiding is due to its systemic threat to the economic security of the state and a high level of latency. Illegal seizure of assets of business entities through falsification, manipulation and abuse is a complex criminal activity that requires comprehensive legal and forensic countermeasures. Effective investigation of raiding crimes is impossible without systematic and professional application of special knowledge. The article purpose is to determine how to reveal the definition of the concept of special knowledge used during the investigation of criminal offenses related to raiding, to determine their typical forms. Based on the conducted searches, it is proposed that special knowledge used during the investigation of criminal offenses related to raiding be understood as knowledge in the field of a specific science, acquired in the process of acquiring professional qualifications, as well as during the conduct of professional activities, which are used by knowledgeable persons to solve those tactical tasks that are beyond the professional competence of the prosecution (most often this is knowledge in the field of economics, accounting, handwriting, linguistics, psychology, computer science, etc.). Typical forms of specific expertise application in investigated criminal offenses are identified and characterized.